Mbonalelo kha vhurangaphanda ha vhafumakadzi: young Vhavená¸“a women's views on their traditional leadership roles historically and post-1994 - Nengwekhulu, Omphulusa (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This is a qualitative research study that examines how young Vhavená¸“a women in post-apartheid South Africa views different traditional leadership roles that Vhavená¸“a women have historically played and continue to play in Vená¸“a society. Therefore, the research question that this Master of Arts (MA) research study sought to research is the following: How do young, 21st-century Vhavená¸“a women view the traditional leadership roles historically and currently held by Vhavená¸“a women in Vhavená¸“a society? To grapple with this research question, this study employed a combination of purposive and snowball sampling strategies to recruit seven research participants. Research participants were interviewed using a semi-structured interview approach, which allowed the researcher to build rapport with research participants. Data was manually coded into five themes, namely: 1) The Role of Makhadzi in Traditional Leadership Among the Vená¸“a Community, 2) The Role of Vhakoma in Traditional Leadership Among the Vená¸“a Community, 3) The Role of Vhakololo in Traditional Leadership Among the Vená¸“a Community, 4) The customary practice of male primogeniture and how it contradicts the South African Constitution post-1994, and 5) The socialisation process that puts boys and men on a leadership pedestal. The data was then analysed and discussed in Chapters Four and Five through an Africana Womanist theoretical framework. An important finding in this study is that makhadzi, the father's sister and also a woman who is a custodian of traditional leadership, is the traditional role that all the participants recognised as the leadership role that Vhavená¸“a women have historically played and continue to play. Another role identified by participants as significant within the Vená¸“a leadership structure is Vhakoma, the Queen Mother and the chief's mother. However, there was limited familiarity with the role of Vhakololo, the royal members or people born into the royal family, as only one participant identified it as a leadership role traditionally occupied by Vhavená¸“a women. Research participants suggested that colonial modernity contributes to a lack of knowledge about their culture. Another important finding of this study is that in post-1994 South Africa, there has been a tension between customary practices such as male primogeniture and the South African Constitution. Consequently, some women leaders have used the courts to challenge this practice. Ultimately, this study contributes to the discourse about women's empowerment and the dismantling of patriarchal structures that undermine women's potential as leaders in the Vená¸“a context.
Keywords: Chiefdoms -- South Africa; South Africa Politics and government 1994-; Colonialism; Apartheid -- South Africa; Primogeniture -- South Africa; Patriarchy -- South Africa